Development of Enhanced Coal Briquettes for Domestic Cooking Applications in Nigeria - ADO, Abubakar D.; MAHMUD, Aminu D.; HARUNA, Jamilu; DODO, Sadiq S.; YAHAYA, Abdullahi (FUDMA Journal of Engineering and Technology, 2026)
This study investigates the development of enhanced coal briquettes for domestic cooking applications in Nigeria, targeting a cleaner and affordable alternative to firewood and charcoal. Coal fines were briquetted with starch as a binder and calcium hydroxide [Ca(OH)₂] as an additive in graded proportions, yielding five formulations (F1–F5) with Ca(OH)₂ content varying from 5% to 25% at a constant 5 g of starch. The formulations were evaluated for ignition time, burning duration, ash content, and calorific value using standard laboratory procedures. A techno-economic assessment was conducted to benchmark production costs against prevalent household fuels. Results indicate that increasing Ca(OH)₂ content progressively delayed ignition (10–32 s), extended burning duration (19–45 min), and raised ash content (10–22%). Formulation F4 (20% Ca(OH)₂) provided the most balanced performance: acceptable ignition time ( 25 s), extended burning duration ( 38 min), moderate ash content ( 13%), and calorific value of 28 MJ/kg. Estimated raw-material costs ( ₦325/kg) are competitive with charcoal and kerosene. These findings indicate that enhanced coal briquettes can serve as a pragmatic transition fuel for low-income and rural Nigerian households where access to LPG is limited.